To solve the quadratic equation \( 46x^2 - 138x = 0 \) by factoring out the greatest common factor (GCF), we first identify the GCF of the terms.
The GCF of \( 46x^2 \) and \( -138x \) is \( 46x \). So, we can factor it out:
\[ 46x(x - 3) = 0 \]
Now, we set each factor equal to zero:
- \( 46x = 0 \) which gives \( x = 0 \)
- \( x - 3 = 0 \) which gives \( x = 3 \)
Thus, the solutions to the quadratic equation are:
\[ x = 0 \quad \text{and} \quad x = 3 \]
Therefore, the correct response is:
The solutions are \( x = 0 \) and \( x = 3 \).